Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.3710
|View full text |Cite
|
Sign up to set email alerts
|

SAT0296 Relationship between disease activity index scores and subjective assessments in early systemic lupus erythematosus

Abstract: As compared to the incidence in general French population, invasive PI was 26 times more frequent in SLE patients. PI occurred at a younger age (43.5+14.9 versus 65.3+18.7 years, p=0.009) and was more severe, with a higher frequency of invasive infection (p<0.001) and higher need for ICU admission (p=0.015) in SLE as compared to non SLE patients. Of note, unusual PI sites, including pneumococcal endocarditis (n=1), arthritis (n=1) and peritonitis (n=1) were observed in SLE patients only. Risk factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Consistent with previous studies, both SLED-R and SLED-O demonstrated weak correlations with PtGA compared to the more robust correlations between SLED-R or SLED-O and PGA. 53,54 Also consistent with previous studies, PtGA scores were more frequently greater than PGA scores. 30,39 Surprisingly, the SLED-R and SLED-O correlations with PtGA were not significantly different.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies, both SLED-R and SLED-O demonstrated weak correlations with PtGA compared to the more robust correlations between SLED-R or SLED-O and PGA. 53,54 Also consistent with previous studies, PtGA scores were more frequently greater than PGA scores. 30,39 Surprisingly, the SLED-R and SLED-O correlations with PtGA were not significantly different.…”
Section: Discussionsupporting
confidence: 91%